Design of a TB MediBox Prototype as a Reminder and Monitoring of Medication Taking in Pulmonary Tuberculosis Patients - Usman, Julianti Isma Sari (Jurnal Teknokes, 2025)
Appropriate and complete TB treatment it is very important to ensure TB bacteria are killed effectively and prevent recurrence disease. If treatment is not followed properly, TB bacteria can become resistant to medication, and difficult to treat. TB sufferers who receive appropriate and complete treatment usually recover completely. As an effort to increase medication compliance in patients TB requires technological innovation, one of which is by making a box prototype design a drug called MediBox TB. Therefore, this study aims to remind TB Patients to take medication regularly with the alarm on the MediBox TB and know the amount of medication consumed.  Research on designing the TB MediBox Prototype as a Reminder and Monitoring of Medication Taking in Pulmonary Tuberculosis Patients has a number of important contributions, both in the health and technology fields, especially in the context of increasing medication compliance and patient monitoring. The research method uses an experimental approach Laboratory-based research and development consists of two stages, namely the design stage tools and tool testing. This tool is designed using a microcontroller-based method Arduino as a device controller and RTC alarm as a time reader. The level of accuracy is assessed of the component's ability to work according to its function, this is influenced by time and sign warning. This prototype shows that it can detect when testing is carried out and There is an alarm sign on the LCD panel display which indicates the device is capable of reading and detect tool components according to instructions. Then to assess the quality of the automatic medicine box that we have designed, we distributed questionnaires to 50 respondents. This questionnaire aims to measure their satisfaction with various aspects of the device. The average score shows a good level of satisfaction in the aspects of ease of use and alarm quality with an average value of 4.08 and 4.06, while the lower average score is in the aspect of battery life with an average value obtained of 3.92. The average score for each aspect is calculated from a scale of 1 (very dissatisfied) to 5 (very satisfied). The results of this study show that the MediBox TB automated medication box, offers features that have great potential to improve the user experience in following the medication schedule.